Anarchy, war, or revolt? Radical perspectives for climate protection, insurgency and civil disobedience in a low-carbon era. (April 2022) - Sovacool, Benjamin K.; Dunlap, Alexander
Abstract: What radical tactics might those seeking transformational action on climate or environmental sustainability undertake? What options are capable of stopping actors and institutions who already realize their actions and behavior may harm millions, degrade the biosphere, and contaminate the climate, but continue to do so, despite the scientific or moral reasons not to? This paper explores efforts that can vigorously confront apathy and inaction and potentially subvert power relations currently perpetuating climate catastrophe and environmental destruction. We examine the tactics employed over time from civil disobedience and (strict) nonviolence, antiauthoritarian strategies and self-defense as well as guerrilla warfare perspectives, and distill from them options for potential climate action. In doing so, we offer a comprehensive inventory of 20 distinct direct action tactics that, while unsavory in some contexts, offer a chance of creating social change. In doing so, we also draw from the wealth of knowledge regarding protests, social movements, self-organization, and an array of different struggles and strategies.